2023
DOI: 10.1111/ele.14241
|View full text |Cite
|
Sign up to set email alerts
|

Early‐life food stress hits females harder than males in insects: A meta‐analysis of sex differences in environmental sensitivity

Abstract: Fitness consequences of early‐life environmental conditions are often sex‐specific, but corresponding evidence for invertebrates remains inconclusive. Here, we use meta‐analysis to evaluate sex‐specific sensitivity to larval nutritional conditions in insects. Using literature‐derived data for 85 species with broad phylogenetic and ecological coverage, we show that females are generally more sensitive to food stress than males. Stressful nutritional conditions during larval development typically lead to female‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…Females are often more sensitive to nutritional stress during the larval stage than males (Teder and Kaasik 2023). This is reflected in our study, where the allometric scaling of female reproductive organs showed more significant plasticity, suggesting that the female reproductive organ development is particularly sensitive to nutritional variations experienced during the larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…Females are often more sensitive to nutritional stress during the larval stage than males (Teder and Kaasik 2023). This is reflected in our study, where the allometric scaling of female reproductive organs showed more significant plasticity, suggesting that the female reproductive organ development is particularly sensitive to nutritional variations experienced during the larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study in Brazil found a higher abundance of winged individuals in forest streams than in oil palm plantations, perhaps owing to reduced resources in oil palm (Cunha et al., 2020). Furthermore, since female insects can be more vulnerable to food stress than their male counterparts (Teder & Kaasik, 2023), change in habitat could affect sex ratios in populations. The proportion of adults to juvenile bugs could also be affected, for example through reduced reproductive success (especially if the number of adult females in a population is reduced due to environmental change), although we are not aware that this has yet been investigated, particularly in semi‐aquatic bugs.…”
Section: Introductionmentioning
confidence: 99%
“…Sex-specific susceptibility to early-life adversity has been demonstrated in some species, with negative associations between harsh developmental conditions and later-life phenotypes apparent in only one sex [24][25][26][27][28]. When longevity differs between the sexes (e.g.…”
Section: Introductionmentioning
confidence: 99%